Scandoromani : remnants of a mixed language - Carling, Gerd (Brill's studies in language, cognition and culture ;, 2014)
This book is the first, comprehensive, international description of the language of the Swedish and Norwegian Romano, also labeled resande/reisende. The language, an official minority language in Sweden and Norway, has a history in Scandinavia going back to the early 16th century. A mixed language of Romani and Scandinavian, it is spoken today by a vanishingly small population of mainly elderly people. This book is based on linguistic, deep interviews with two native speakers of different families (one of whom is the co-author) as well as reviews of earlier sources on Scandoromani. The study reveals a number of interesting features of the language, as well as of mixed languages in general. In particular, the study gives support to the model of autonomy of mixed languages.